Home Respiratory Polygraphy and Spirometry in Normal Weight and Children with Obesity Suspected for Obstructive Sleep Apnea Syndrome: Are There Any Associations?. (31st January 2023) - Corbelli, Regula; Barazzone, Constance; Grasset Salomon, Carole; Beghetti, Maurice; Maggio, Albane B. R.
Abstract : Aim . It is known that children and adolescents with obesity are more prone to obstructive sleep apnea syndrome (OSAS) and that their lung function may show some disturbance. Literature is scarce about potential associations; therefore, we aimed to study the relationship between OSAS, lung function, and adiposity in a population of children suspected of OSAS. Material and Methods . We performed home respiratory polygraphy and spirometry in all subjects. The relationships between body mass index z -score (zBMI), polygraphy, and spirometry data were analyzed. Results . We recruited 81 subjects aged between 5 and 16 years, 63% being obese. 43.2% of subjects were diagnosed with OSAS (32.1% mild, 4.9% moderate, and 6.2% severe). We found no correlation between respiratory polygraphy and the zBMI. The mean spirometric value FEV1, FVC, and FEV1 /FVC ratio z 's were normal in all subjects, whereas FVC z 's and FEV1 /FVC ratio z 's were significantly positively related for obesity and negatively for normal weight (p < 0.05 ). FEV1 z 's was inversely correlated to the percentage of analyzed time passed below 90% of SpO2 (r = − 0.224, p = 0.044 ). All subjects with FEV1 (n = 8 ) and/or FVC (n = 9 ) z 's below the lower limit for normal (LLN) had an AHI ≥ 1 (FEV1 : p = 0.001 ; FVC: p < 0.001 ), especially subjects with normal weight (FEV1 : p = 0.003 ; FVC: p = 0.010 ). Conclusion . When comparing normal-weight children and adolescents with obesity, the prevalence of OSAS but not spirometric values was strongly related to BMI z -score, probably because obesity engenders advanced puberty and an accelerated growth spurt. FEV1 was more frequently <LLN in normal-weight children, while obese subjects presented low FEV1 /FVC ratio z 's and FEF25-75% z 's. Moreover, all subjects with abnormal spirometric values were suffering from at least mild OSAS, again more frequently in normal-weight subjects.